(untitled) (Research, Society and Development, 2023)
Environmental biotechnology is the set of techniques that use organisms or parts of them to monitor, prevent and restore environments. In this sense, this work aimed to understand the current scenario of scientific research in environmental biotechnology carried out in the northern region of Paraná, highlighting the weaknesses and potentialities. To this end, a systematic review of the literature hosted on the Capes Periodicals Portal was carried out, using Boolean descriptors and operators previously selected for this purpose. The results indicate the impressive performance of Public Universities in Northern Paraná, in addition to revealing the predominance of work related to the quality of aquatic ecosystems and the use of distinct biomarkers and bioindicators, to collect a broad spectrum of data about the analyzed environments. Several types of organisms, from different taxa, have been used as indicators of environmental quality; as well as a wide range of markers. It is clear that environmental biotechnology can provide tools to resolve environmental contamination, offering efficient treatments. As several of these techniques are still in the development phase, their widespread use is not yet fully widespread.